Calcific Tendinitis of the Rotator Cuff: A Randomized Controlled Trial of Ultrasound-Guided Needling and Lavage Versus Subacromial Corticosteroids. (July 2013) - de Witte, Pieter Bas; Selten, Jasmijn W.; Navas, Ana; Nagels, Jochem; Visser, Cornelis P.J.; Nelissen, Rob G.H.H.; Reijnierse, Monique
Background: Calcific tendinitis of the rotator cuff (RCCT) is frequently diagnosed in patients with shoulder pain, but there is no consensus on its treatment. Purpose: To compare 2 regularly applied RCCT treatments: ultrasound (US)–guided needling and lavage (barbotage) combined with a US-guided corticosteroid injection in the subacromial bursa (subacromial bursa injection [SAI]) (group 1) versus an isolated SAI (group 2). Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients were randomly assigned to the 2 groups. Shoulder function was assessed before treatment and at regular follow-up intervals (6 weeks and 3, 6, and 12 months) using the Constant shoulder score (CS, primary outcome), the Western Ontario Rotator Cuff Index (WORC), and the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH). Additionally, calcification location, size, and Gärtner classification were assessed on radiographs. Results were analyzed using the t test, linear regression, and a mixed model for repeated measures. Results: This study included 48 patients (25 female, 52.1%; mean age, 52.0 ± 7.3 years; 23 patients in group 1) with a mean baseline CS of 68.7 ± 11.9. No patients were lost to follow-up. Four patients in group 1 and 11 in group 2 ( P = .06) had an additional barbotage procedure or surgery during the follow-up period because of persisting symptoms and no resorption. At 1-year follow-up, the mean CS in group 1 was 86.0 (95% CI, 80.3-91.6) versus 73.9 (95% CI, 67.7-80.1) in group 2 ( P = .005). The mean calcification size decreased by 11.6 ± 6.4 mm in group 1 and 5.1 ± 5.7 mm in group 2 ( P = .001). There was total resorption in 13 patients in group 1 and 6 patients in group 2 ( P = .07). With regression analyses, correcting for baseline CS and Gärtner type, the mean treatment effect was 20.5 points ( P = .05) in favor of barbotage. Follow-up scores were significantly influenced by baseline scores. Results for the DASH and WORC were similar. Conclusion: On average, there was improvement at 1-year follow-up in both treatment groups, but clinical and radiographic results were significantly better in the barbotage group.